LITERATURE STUDY REPORT LEVERAGE RATIO ANALYSIS, ACTIVITY RATIO AND PROFITABILITY RATIO TO FINANCIAL DISTRESS CONDITIONS PT INDOFOOD SUKSES MAKMUR TBK - Benedictus Putut Bayu Woro - (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
This research was conducted with the aim of analyzing the factors that influence the financial distress conditions of PT Indofood Sukses Makmur TBK. This study analyzes the effect of ratios, activity ratios and profitability ratios on stock underpricing. The analytical method used is the literature review method. The results showed that financial distress can be predicted by using financial ratios, namely the leverage ratio, activity ratio, and profitability ratio to prevent company bankruptcy. Furthermore, symptoms of financial disruption from an early age can prevent bankruptcy. For researchers who carry out research in the same field, it is expected to use different variables to calculate the ratio to be able to see from another point of view the effect that occurs, or to add other variables.